Do movimento da Matemática Moderna à BNCC: Alterações curriculares do Ensino de Geometria nos anos finais do Ensino Fundamental - Silva, Noemita Rodrigues da (2020)
This study aims to observe the curricular changes in the teaching of geometry in the last years of elementary school, based on educational documents ranging from the Movement of Modern Mathematics (MMM) to the approval of the National Common Curricular Base (BNCC), making the comparison of theoretical assumptions that govern pedagogical practices and their relationship with the development of geometry teaching present in the analyzed documents. The methodology of this work is a bibliographic and documentary research, which is characterized by the analysis and interpretation of the normative documents of the basic education curriculum, they are: the PCN, launched in 1998, and the BNCC final version, 2018, in addition to them, the epistemological studies about the theoretical factors covered in our study: curriculum, skills, MMM and the geometry of the last years of Elementary School. In search of a better approach to the theme, we opted for a theoretical foundation that guides curriculum analysis, in order to broaden the understanding of what is and what the importance of curricula, in addition, it‘s different meanings, it‘s growth, that how the curricula are present in the teaching and learning processes through the levels of development and, finally, the role of BNCC as a guiding document, or even, the relationship between curriculum, school and classroom. We seek an understanding of the use of skills in the documents worked on in this research, as well as how they are dialogued by researchers, in order to understand what their implications are for teaching geometry. In this context, we can observe that the role of the curriculum is essential to understand the behavior of teaching geometry from the MMM period until the approval of the BNCC, as well as the intentionality of the normative documents in the concept of competences and skills. Furthermore, we can also verify that MMM guided a pedagogical activity mainly concerned with formalizations, distancing itself from practical issues, from their applicability in daily life. We also analyze that in the part related to geometry, it was initially concerned with introducing logical reasoning. In short, we point out that the teaching of geometry has undergone few changes, but were important changes for the curriculum.